2004
DOI: 10.1002/pssb.200402067
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar interaction energy for a system of magnetic nanoparticles

Abstract: PACS 75.75.+a, 75.40.Mg The long range dipolar interaction energy of a system of single domain magnetic particles with randomly oriented spins and easy axes is calculated by a direct space summation method based on the Lekner formalism. The method is useful for the numerical simulations of positionally disordered nanomagnetic arrays which are being widely used for these systems and is easily adapted for any geometry of the simulation cell. The summations are rapidly convergent, requiring only a few terms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Others have reported that the method fails for slab nanosheet (2D + h) geometries and simple nanostructures. 5 When there is an interest in exploring the rate of convergence to a bulk value, an alternative approach that is often used is called "the method of expanding cubes" (EC) which takes various forms. [6][7][8] Most recently, papers by Gaio and Silvestrelli (GS) 8 and by Harrison 4 have focused on improving EC convergence rates obtained by adopting spherical or cubic expansions around a central core, and applying a suitable Q/R charge correction.…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported that the method fails for slab nanosheet (2D + h) geometries and simple nanostructures. 5 When there is an interest in exploring the rate of convergence to a bulk value, an alternative approach that is often used is called "the method of expanding cubes" (EC) which takes various forms. [6][7][8] Most recently, papers by Gaio and Silvestrelli (GS) 8 and by Harrison 4 have focused on improving EC convergence rates obtained by adopting spherical or cubic expansions around a central core, and applying a suitable Q/R charge correction.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper of this journal, S. Lamba derived a Lekner type summation of the dipolar interaction energy for magnetic nanoparticles systems [1]. He also presented that the results can be used in Monte Carlo simulation.…”
mentioning
confidence: 97%
“…It must be noted that the dipolar system Lekner considered is only 2-dimensional periodic and in 3-dimensional periodic system, Lekner calculated the force directly rather than energy. Equations (12) and (13) of S. Lamba [1], namely the double sum Ref. [3].…”
mentioning
confidence: 99%
“…The dipolar interaction energy between a pair of finite sized magnetic particles, as expressed in Eqs. (1) and (2) of the original article [1] obviously assumes a finite separation between the particles, i.e. the distance between the i-th and j-th particle 0 ij r > and the term i j = is excluded from the summation.…”
mentioning
confidence: 99%
“…In the article "Dipolar interaction energy for a system of magnetic nanoparticles" [1] the dipolar energy for a system of single domain magnetic particles was calculated, based on the summation techniques used by Lekner for two dimensional and quasi two dimensional systems.…”
mentioning
confidence: 99%